Assessing the Impact of Extreme Temperature Conditions on Social Vulnerability - Ibolya Török (Sustainability, 2021)
This research aims to improve the existing methodology by quantifying the effects of climate change on social vulnerability by developing a set of vulnerability indicators. It delimits for the first time in Romania the most vulnerable areas from this point of view and facilitates the decision-making processes and planning efforts targeting the increase of resilience and adaptive capacity of local communities. We selected 35 variables and constructed four aggregated indexes by applying the principal component analysis, and then the Climate-Related Social Vulnerability index (CleSoVI) index was derived. It pointed out that the most significant impact on the vulnerability of settlements in the test region (Cluj County) can be attributed to the lack of adaptive capacity and increased poverty. The most vulnerable areas are located in the northern and south-eastern parts of the county. From a socio-economic point of view, local authorities’ efforts should reduce the vulnerability of these regions and prepare them to cope with and adapt to the impact of climate change.